KESIAPAN PETANI MENGIKUTI SERTIFIKASI KOPI ORGANIK DI KABUPATEN LAMPUNG BARAT - Izuddin Gustoro; Fembriarti Erry Prasmatiwi; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to analyze the readiness of farmers, their income, and marketing of certified organic coffee in West Lampung Regency. This research conducted in Sindang Pagar Village, Sumber Jaya Sub-District, Mutar Alam Village and Tambak Jaya Village, Way Tenong Sub-District, West Lampung Regency. The samples of this research were all farmers participating in the organic coffee certification program, 35 farmers totally. Qualitative descriptive analysis used to analyze the readiness of farmers in participating the certification program, quantitative descriptive analysis used to calculate farm income, marketing channels, and marketing margins. The results showed that the farmers were not ready to take part in the organic certification program because there were still unfulfilled indicators. Organic coffee farming income is IDR3,741,918 per ha with an R/C value of 1.74. Coffee marketing in this research area has 3 marketing channels. In marketing channel I farmers sell their coffee to coffee processors, in marketing channel II farmers sell to wholesalers then to exporters, in marketing channel III coffee farmers sell to collectors, then to wholesalers, and finally to exporters. The selling price in the first channel is more profitable for farmers than the second and third channels. Marketing carried out by farmers participating in the certification, namely 18% is sold at the price of organic coffee, and the remaining 82% sold underpriced. In the second and third channels, farmers do not get a premium fee for marketing the coffee products they produce during the certification process.Key words: coffee, certification, farmers, organic.